Typhoid burden, drug resistance and Pakistan’s stance against it - Ali, Nouman Mansoor; Nasr, Rabail; Rehman, Mehroze; Mahmood, Syed Uzair (International Journal Of Community Medicine And Public Health, 2021)
Salmonella typhi is a gram negative, rod shaped bacteria that features a polysaccharide capsule, flagella for motility and fimbria for adhesion to the epithelial cells of intestinal mucosa. The organism is responsible for causing enteric fever and in severe cases it leads to complications such as intestinal perforation which can lead to death. The mainstay of treatment of typhoid fever is antibiotic therapy but unfortunately the emergence of MDR (multidrug resistant) and XDR (extensively drug resistant) strains pose a major threat to the successful treatment of typhoid. Around 200,000 global deaths can be associated with typhoid and most cases are seen in low socioeconomic countries with inadequate healthcare infrastructure particularly those that are densely populated, among them Pakistan is considered as high-risk country according to WHO criteria. Prevention strategies include education of the masses regarding hand hygiene, cleanliness and consumption of clean food and water. In 2019 Pakistan encountered an epidemic of XDR typhoid and to control it, Government introduced typhoid vaccine in its nationwide vaccination program, and is hopeful that it will decrease the burden of disease on state and its citizens.